2014
DOI: 10.1002/jcb.24699
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1-Mediated Inflammation and Growth Activated & Inhibited Transition Mechanisms Between No-Tumor Hepatitis/Cirrhotic Tissues and HCC

Abstract: To understand breast cancer 1 early onset (BRCA1)-mediated inflammation and growth activated and inhibited transition mechanisms between no-tumor hepatitis/cirrhotic tissues (HBV or HCV infection) and human hepatocellular carcinoma (HCC), BRCA1-activated different complete (all no positive correlation, Pearson correlation coefficient <0.25) and uncomplete (partly no positive correlation except BRCA1, Pearson <0.25) networks were identified in higher HCC compared with lower no-tumor hepatitis/cirrhotic tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Studies have found that Brca1 induced cell apoptosis mediated by ERK1/2 activation ( 44 ) and P53 signaling ( 45 ). Brca1 mediates the inflammatory response between no-tumor hepatitis/cirrhotic tissues and hepatocellular carcinoma ( 46 ). However, Singh et al ( 47 ) found that BRCA1 expression was attenuated in the plaque region of human atherosclerotic carotid artery samples, and Brca1 deficiency led to greater inflammation-associated apoptosis and impaired endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that Brca1 induced cell apoptosis mediated by ERK1/2 activation ( 44 ) and P53 signaling ( 45 ). Brca1 mediates the inflammatory response between no-tumor hepatitis/cirrhotic tissues and hepatocellular carcinoma ( 46 ). However, Singh et al ( 47 ) found that BRCA1 expression was attenuated in the plaque region of human atherosclerotic carotid artery samples, and Brca1 deficiency led to greater inflammation-associated apoptosis and impaired endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR_1- activatory different mutual-positive-correlation molecular Pearson coefficients were computed in high lung adenocarcinoma compared with the corresponding low human normal adjacent tissues under EGFR_1 CC ≥0.25 17 , 19 , 20 .…”
Section: Methodsmentioning
confidence: 99%
“…BIK-activatory different mutual-positive-correlation molecular Pearson coefficients were computed in low normal adjacent tissues compared with the corresponding high lung adenocarcinoma under BIK CC C0.25 [15,17,18].…”
Section: Methodsmentioning
confidence: 99%